Does sell-side debt research have investment value?. Issue 3 (16th April 2023) - Choi, Sunhwa; Kim, Robert
Abstract : This study examines whether sell-side debt research has investment value for debt investors. We find that both the levels of and changes in recommendations are associated with event-time abnormal bond returns, and that changes in recommendations (i.e. upgrades and downgrades) are associated with stronger price reactions. More importantly, we find that changes in recommendations are associated with a significant post-event bond price drift, suggesting delayed market reactions to recommendation changes. The calendar-time portfolio approach of buying (selling) bonds following upgrades (downgrades) generates significant abnormal bond returns. In addition, we present new evidence that debt analysts often provide different recommendations for bonds issued by a firm to reflect different bond-specific characteristics. Overall, our results suggest that debt analysts' recommendations have investment value.